Peningkatan hasil belajar siswa SMK melalui pengembangan e-modul berbasis EPUB berbantuan kotobee - Erlista Maulidhea Vara; Mohammad Arief (Universitas Negeri Malang, 2022)
The development of technology in the educational aspect has developed rapidly with the availability of learning materials which are easy to operate so it can improve student’s learning outcomes. This research aims to develop an EPUB-based E-Module that tested to be feasible and effective through the expert validation tests and can improve OTKP students’ learning outcomes in SMKN Mojoagung. The method used in this study is R & D or Research and Development by using ADDIE model.The subjects of this research are material expert, module expert, and students of class X OTKP SMKN Mojoagung. There are two types of data used in this research; quantitative and qualitative which obtained from interview, questionnaires, and tests. The students’ learning outcomes are analyzed using normality test and independent sample t-test. This research produces an E-Module in 2nd semester Correspondece subject of class X OTKP which contains interactive contents and features to attract students’ learning interest. The developed E-Module is said to be very feasible through the validation by material expert, module expert, and small group trial. In addition, the Correspondence E-Module is said to be effective as evidenced by the significant difference of students’ learning outcomes between the experimental class, that use E-Module, and control class, who didn’t use it. In the cognitive aspect, the average of the student’s learning outcomes was 86.72 which was higher that the control class that reached 82.00. Similar to cognitive scores, the psychomotor score of the experimental class are also higher than the control class. Based on the research conducted, it is recommended that the Correspondence E-Module can be used as learning material for students. In addition, it is recommended to teachers use this to help studens’ interest in learning independently. Perkembangan teknologi dalam dunia pendidikan sudah berkembang pesat dengan tersedianya bahan pendukung belajar yang mudah digunakan sehingga dapat meningkatkan hasil belajar. Penelitian ini bertujuan untuk menghasilkan E-Modul berbasis EPUB yang teruji layak dan efektif melalui uji validasi ahli materi dan ahli modul serta mampu meningkatkan hasil belajar peserta didik kelas X OTKP SMKN Mojoagung. Metode yang digunakan adalah metode R & D atau Research and Development dengan menggunakan model ADDIE. Subjek uji coba penelitian ini terdiri dari ahli materi, ahli modul, dan peserta didik kelas X OTKP SMKN Mojoagung. Terdapat dua jenis data dalam penelitian ini yakni data kuantitatif dan data kualitatif yang diperoleh dari hasil wawancara, angket, dan tes. Hasil belajar peserta didik dianalisis menggunakan uji normalitas dan uji independent sample t-test. Penelitian ini menghasilkan E-Modul Korespondensi kelas X OTKP semester genap yang memuat konten-konten dan fitur yang interaktif agar dapat menarik minat belajar peserta didik. Pengembangan E-Modul ini dinyatakan sangat layak melalui uji validasi ahli materi, ahli modul, dan uji coba kelompok kecil. Selain itu, E-Modul Korespondensi juga dinyatakan efektif dibuktikan dengan adanya perbedaan yang signifikan terhadap perolehan nilai hasil belajar antara kelas eksperimen yang menggunakan E-Modul dengan kelas kontrol yang tidak menggunakan E-Modul. Pada aspek kognitif, nilai rata-rata kelas eksperimen sebesar 86,72 lebih tinggi dari kelas kontrol dengan rata-rata sebesar 82,00. Nilai psikomotorik kelas eksperimen juga lebih tinggi dibandingkan kelas kontrol. Berdasarkan penelitian yang dilakukan, disarankan agar E-Modul Korespondensi dapat digunakan sebagai bahan belajar peserta didik. Selain itu, disarankan untuk guru menggunakan E-Modul ini sebagai pendamping dalam mengajar karena E-Modul Korespondensi membantu minat peserta didik belajar secara mandiri.